PENGARUH CURRENT RATIO DAN TOTAL ASSET TURN OVER TERHADAP RETURN ON EQUITY PADA PT INDOFOOD CBP SUKSES MAKMUR TBK PERIODE 2013-2024 - Avif Khanafi; Dira Karlina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine The Effect of Current Ratio and Total Asset Turn Over on Return on Equity at PT Indofood CBP Sukses Makmur Tbk for the 2013-2024 Period, both partially and simultaneously. The research method used is descriptive quantitative. The data used are secondary data in the form of financial reports of PT Indofood CBP Sukses Makmur Tbk for the 2013-2024 Period, obtained through the BEI (Indonesia Stock Exchange). The analysis methods used are descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of the study show that partially the Current Ratio (X1) does not affect Return On Equity (Y) as seen from the results of the t-test which shows the Current Ratio (X1) with a significant value of >0,05, namely 0,170. Partially the Total Asset Turn Over (X2) affects Return On Equity (Y) as seen from the results of the t-test which shows the Total Asset Turn Over (X2) with a significant value of <0,05, namely 0,003. Simultaneously the Current Ratio (X1) and Total Asset Turn Over (X2) have a significant effect on Return On Equity (Y). This can be seen from the significant value of 0,002 while for the F table it is 4,10 so that the calculated F is 13,913 > F table of 4,10 (13,913 > 4,10) and the results of the determination coefficient show that the Current Ratio and Total Asset Turn Over on Return On Equity have an effect of 0,701 or 70,1% while the remaining 29,9% is influenced by other variables outside this regression model.